Hubungan Antara Lokasi Lesi Pada Stroke Akut Terhadap Kejadian Disfagia Di RSUD Dr. Saiful Anwar Provinsi Jawa Timur - Kartika Sari, Wahyu Dwirima (PERDOSNI, 2025)
Introduction: Dysphagia is a common complication following acute stroke, occurring in approximately 28-65% of cases and posing significant risks such as aspiration, pneumonia, and prolonged hospitalization. Previous studies have identified associations between acute stroke and dysphagia, implicating various brain regions. Aim: This study aimed to explore the correlation between lesion location and dysphagia in acute stroke patients treated at RSUD Dr. Saiful Anwar, East Java. Metode: The study employed the Swallowing Swallowing Screening (GUSS) questionnaire to detect dysphagia in acute stroke patients. Lesion location analysis utilized the chi-square test to differentiate between strategic and non-strategic areas. Results: Data from July to September 2023 included 35 samples, comprising 22 males (62.9%) and 13 females (37.1%). Ischemic stroke accounted for 25 cases, while hemorrhagic stroke accounted for 10. Among ischemic stroke patients, only one exhibited dysphagia, compared to two in the hemorrhagic stroke group. These findings align with prior research, indicating a higher prevalence of dysphagia in hemorrhagic strokes, particularly those involving the cerebral hemisphere and intraventricular extension. Statistical analysis using the Fisher Test did not demonstrate a significant association between lesion location and dysphagia in either ischemic or hemorrhagic strokes (p > 0.05). Discussion: This study found no significant relationship between lesion location and dysphagia incidence in acute stroke patients at RSUD Dr. Saiful Anwar. Further research with a larger sample size is warranted to validate these findings and explore additional factors influencing post-stroke dysphagia. Keywords: Dysphagia, GUSS (Gugging Swallowing Screen), acute stroke, lesion